TEACHING ENGLISH TO YOUNG LEARNERS - Kurbonova, Gulmera (INTERNATIONAL CONFERENCES, 2022)
Language is a means of communication. In the last decades English takes a place as a global lingua franca, in particular the political and social connections. It plays a great role in social relationship. And the English language is the first and essential language that we teach to children at very early stages of schooling.